2019
DOI: 10.1124/mol.118.114827
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hepatotoxicity of Mithramycin Therapy Caused by Altered Expression of Hepatocellular Bile Transporters

Abstract: Mithramycin demonstrates preclinical anticancer activity, but its therapeutic dose is limited by the development of hepatotoxicity that remains poorly characterized. A pharmacogenomics characterization of mithramycin-induced transaminitis revealed that hepatotoxicity is associated with germline variants in genes involved in bile disposition: ABCB4 (multidrug resistance 3) rs2302387 and ABCB11 [bile salt export pump (BSEP)] rs4668115 reduce transporter expression (P , 0.05) and were associated with $grade 3 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Tests of plicamycin, being already commercially and clinically approved, 60 to confirm its efficacy should be considered as a top priority, to be performed in vitro and in vivo. This should also include the assessment of its side effects such as hepatotoxicity, 61 which despite usually being transient and asymptomatic could limit its therapeutic use in certain patients with limited hepatic function. This is especially relevant in the context of emergency and urgency caused by the 2020 COVID-19 pandemic outbreak.…”
mentioning
confidence: 99%
“…Tests of plicamycin, being already commercially and clinically approved, 60 to confirm its efficacy should be considered as a top priority, to be performed in vitro and in vivo. This should also include the assessment of its side effects such as hepatotoxicity, 61 which despite usually being transient and asymptomatic could limit its therapeutic use in certain patients with limited hepatic function. This is especially relevant in the context of emergency and urgency caused by the 2020 COVID-19 pandemic outbreak.…”
mentioning
confidence: 99%
“…Plicamycin (also known as mithramycin) being already commercially and clinically approved, 31 tests to confirm its efficacity should be considered as a top-most priority, to be performed in vitro and in vivo. This should also include the assessment of its side effects such as hepatotoxicity 32 , that in spite to be usually transient and asymptomatic, it could limit its therapeutic use in certain patients with limited hepatic function. Indeed, the potent RBD/ACE2 inhibition clearly demonstrated in the present work, and the vast knowledge of its pharmacology and pharmacokinetics, studied for decades, 33 known to be very active in lungs and esophagus, 34 makes this drug a very attractive opportunity to treat severe COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, no efficacy was demonstrated. Notable transaminitis was seen within 72 h of treatment, reaching levels up to 500× the upper limit of normal, with resolution often taking 1–3 weeks [ 28 , 29 ]. Recent investigations suggested that the hepatotoxicity was related to the inhibition of farnesoid-X receptor signaling and germline variants in genes involved in bile acid flow and disposition (e.g., ABCB4 and ABCB11) [ 29 ].…”
Section: Recent Clinical Developmentmentioning
confidence: 99%
“…Notable transaminitis was seen within 72 h of treatment, reaching levels up to 500× the upper limit of normal, with resolution often taking 1–3 weeks [ 28 , 29 ]. Recent investigations suggested that the hepatotoxicity was related to the inhibition of farnesoid-X receptor signaling and germline variants in genes involved in bile acid flow and disposition (e.g., ABCB4 and ABCB11) [ 29 ]. Interestingly, the associated hepatic injury was transient, rarely symptomatic, and did not require intervention; however, it significantly hampered the clinical utility of mithramycin [ 21 , 29 ].…”
Section: Recent Clinical Developmentmentioning
confidence: 99%